Transformational Leadership Mediates the Effect of Integrity Zone Implementation on Organizational Commitment: Evidence from PLS-SEM Analysis - Andina Alisya Amanda; Eka Yudhyani; Evi Kurniasari Purwaningrum (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Public organizations are increasingly required to implement integrity-based reforms to improve governance quality and employee commitment. This study examines the effect of integrity zone implementation on organizational commitment and the mediating role of transformational leadership. The research was conducted at an institution actively implementing the integrity zone program to achieve a corruption-free area and a clean and serving bureaucracy. A quantitative approach was employed using Structural Equation Modelling (SEM) with Partial Least Squares (PLS). The results indicate that the integrity zone does not have a significant direct effect on organizational commitment. However, integrity zone implementation significantly enhances transformational leadership, which in turn strengthens organizational commitment. These findings confirm that transformational leadership plays a mediating role in linking integrity zone implementation to organizational commitment. The study highlights the importance of leadership that upholds integrity values in translating organizational policies into employee commitment. This research contributes to the literature by emphasizing that the effectiveness of integrity-based reforms depends not only on formal policy implementation but also on leadership practices that internalize ethical values within organizations.